Hujambo! A Standards-Based Approach to Introductory Kiswahili - Wawire, Brenda (Open textbook library., 2022)
Hujambo! provides a complete curriculum for introductory Kiswahili that chronicles the adventures of two American students studying abroad in Tanzania for an academic year. It is designed for an introductory Kiswahili course at the college level with approximately 150 contact hours of instruction (5 hours a week for two 15-week semesters, or 5 hours a week for three 10-week quarters). It provides a foundational understanding of Kiswahili and the cultures of those who share it as a common language. Students will acquire the basics of Kiswahili grammar and build a core vocabulary of approximately 1,000 words, including the most common words for everyday interactions and the individual vocabulary they need to speak about their own academic and personal lives.